On the cumulant expansion peculiarity for partition function functional of the cluster de Gennes model - Korynevskii, N.A. (Condensed Matter Physics, 2000)
The problem of the functional representation for cluster de Gennes model partition function within the collective variables method is discussed. Contrary to the usual Ising model case the coefﬁcients of the obtained partition function functional (cluster cumulants) depend on temperature T and transverse ﬁeld Γ . Therefore there exists a rigorous limitation on the value of Γ parameter at low temperatures. The equation for maximum value Γl , temperature and short-range intracluster interaction V is obtained. The solutions of this equation have been found.